CORPORAL PUNISHMENT: THE SLAP THAT CARRIES THE MESSAGE OF VIOLENCE - T.S, BINDU; N.S., VIJAYALEKSHMI (THE PRIMARY TEACHER, 2012)
The present article is an endeavour to raise a few important points concerning corporal punishment which breaches children’s fundamental human rights. It is a fact that corporal punishment is often practised in educational institutions to maintain discipline thereby promoting effective behaviour. Corporal punishment is a means of discipline that relies on fear and submissiveness and diminishes a child’s capacity to grow up as an autonomous and responsible person. This paper focuses on the legal provisions of corporal punishment, pros and cons of this aspect and effective guideline in eliminating this ’threat’ to the healthy development and welfare of children